"Like Make Up on a Man": The Gendered Nature of Gun Norms. Issue 3 (3rd March 2020) - Mullins, Christopher W.; Lee, Sou
ABSTRACT: Prior research has established that women involved in criminal social networks and streetlife subculture tend to have high levels of personal victimization. Despite high levels of risk, and an apparent wide availability, these women typical neither carry nor use firearms, specifically handguns. Drawing upon interviews with 31 criminally involved women, this paper explores these women's victimization experiences and their experiences with, and attitudes towards, firearms, especially handguns. Overall, we find that many norms held by women towards firearms in mainstream culture are shared by their peers involved in streetlife subculture.